Concept innovation paradigm synergy - Ільїн, В.В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2012)
The paper analyzes the problem of innovation main features of modern socioeconomic development. The attention to innovative thinking, akin to synergy, a new paradigm of thinking and cognition.